Conditions of stability loss during the test of hydraulic forming of drawpieces. Part I. Derivation of basic equations and relationships. Part II. Discussion and analysis of the results - Śloderbach, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
Part I: The paper contains two parts. In the first part, basic relationships were derived and some problems connected with stability loss during hydraulic forming of round metallic drawpieces with liquid pressure were discussed. The aim of the considerations is to test drawability of sheets by estimation of acceptable values of plastic strains and the corresponding heights of spherical shells. The analysis was based on some selected real conditions of stability loss. The influence of the coefficient of material hardening for the drawpiece, the coefficient of normal anisotropy and coefficients of plane anisotropy on acceptable values of plastic strains and heights of the formed drawpieces corresponding to the given condition of stability loss was also tested.
Keywords: hydraulic forming; stability loss; boundary strains; height of drawpieces; normal anisotropy; plane anisotropy